Effect of Vanadium on the Phase Transformation Behavior of Ti–Mo Microalloyed Ultra‐High Strength Steel. Issue 9 (11th June 2018) - Gan, Xiaolong; Yang, Gengwei; Zhao, Gang; Mao, Xinping; Huang, Huihui; Xu, Guang
Abstract : Vanadium is a vital microalloying element in the precipitation hardening of hot‐rolled high strength steel. Its effects on the continuous cooling phase transformation behavior, microstructure, and properties of Ti–Mo and Ti–Mo–V microalloyed ultra‐high strength steels are studied by the thermal simulator, scanning electron microscopy (SEM), high‐resolution transmission electron microscopy (HRTEM), energy dispersive spectrometer (EDS), and electron backscatter diffractometer (EBSD). The dynamic continuous cooling transformation curves are obtained which show that vanadium can restrain the ferrite‐pearlite and bainite transformation, refine the microstructure, and harden the steel matrix. It is also found that the strain‐induced precipitation of nano‐sized (Ti, Mo) C and (Ti, V, Mo) C particles, with NaCl type structure, exists in Ti–Mo and Ti–Mo–V steel, respectively, as identified by the HRTEM and EDS. And the lattice constants of (Ti, Mo) C and (Ti, V, Mo) C are 0.432 and 0.430 nm, respectively. The higher hardness of Ti–Mo–V steel is attributed to the grain refinement and precipitation hardening by the nano‐sized (Ti, Mo, V) C particles. Abstract : The effects of V on the continuous cooling phase transformation behavior, microstructure, and properties of Ti–Mo and Ti–Mo–V microalloyed ultra‐high strength steels are investigated. The dynamic continuous cooling transformation curves are obtained which show that vanadium can restrain the ferrite‐pearlite and bainite transformation.